Establishment of Green Chemistry Awareness Instrument for secondary school students - Che Nidzam Che Ahmad; Asmayati Yahaya; Rozita Yahaya; Hafsah Taha; Mohd Mokhzani Ibrahim (Institute of Advanced Engineering and Science, 2022)
The purpose of the study was to develop a valid and reliable instrument that can assess green chemistry awareness among secondary schools. This study applied a quantitative approach with a survey design to obtain information related to items and constructs to build an instrument to access student awareness of green chemistry. The study population involved all form four students who are taking a chemistry subject in 85 secondary schools in the State of Melaka, Malaysia. This study involved two phases and all the respondents were selected using a random sampling method. The first phase involved 700 respondents and the second phase involved 500 respondents. The pilot study involved 100 students who were also randomly selected from the same population but not involved in phase I and phase II study. The data obtained were analyzed using Statistical Package for Social Science (SPSS) software. As a result, the Green Chemistry Awareness Instrument (GCAI) was developed. GCAI contains six constructs with a total of 29 items; knowledge (eight items), attitudes (six items), value (eight items), and awareness lighting (seven items). GCAI was found to have good content and construct validity as well as high reliability. Hence, it can assess green chemistry awareness among secondary school students. GCAI also has the advantage of being easily administered.